Belajar dari Pasang Surut Peradaban Borobudur dan Konsep Pengembangan Pariwisata Borobudur - M. Baiquni (Forum Geografi, 2009)
Borobudur is a famous tourism destination which is listed as a World Heritage Site listed in 1991. Recently the condition of the temple is threatened with many problems related to tourist behaviors, overcrowded vendors and traders, as well as managerial issues. This research was carried out with literature study, field observation, peer discussion and seminar. Reflecting the history, this research tried to explain the rise and fall of civilization. This research tried to explain Borobudur as magnet for tourism destination and tourism as locomotive for community and regional development. There are five reasons why glory of civilization can fall even dramatically: (1) horizontal conflicts among social groups; (2) intrigue and struggle for power among elite leaders; (3) expansion and occupation from foreign power; (4) environmental degradation; and (5) disasters like volcanic eruption, earthquake and tsunami. Borobudur has many enigmas, when and why the fall of its civilization. It is not easy to explain these enigmas. The results of this research are: (1) it is possible combination of causes the fall of Borobudur civilization, but the most possible was volcanic eruptions of Merapi. (2) Borobudur has problems related to the tourist number who disturb the stone relief and statues when they climb up the temple (3) Tourists disappointed to lack of hospitality and low quality of services provided by the management as well as the vendors and traders. (4) The problems of conservation related to environmental changes. Among others, prime recommendation is “Rethinking Borobudur” to get new alternative and strategy to manage this world heritage.